PEMBELAJARAN KEWIRAUSAHAAN BERBASIS INOVASI PEMBENTUK PENGUSAHA MUDA DI PERGURUAN TINGGI MUHAMMADIYAH - Beni Dwi Komara; Aries Kurniawan; Putra Panji Respasti; Heru Baskoro (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
Entrepreneurship education is implemented as an elective subject in various tertiary faculties with the aim of producing graduates who become job creators. The rapid growth of entrepreneurship education has been fueled by declining employment and a desire to self-manage. The aims of this research are 1) To find out how to make an entrepreneur education model that is effectively applied. 2) Describe how to measure the success of entrepreneur-based universities in forming young entrepreneurs. 3) Analyze student behavior when implementing the entrepreneurship education model through existing programs. This research includes qualitative research. Data collection resulted from in-depth interviews with 5 batch 2017-2021 entrepreneurship study program students, some of whom are already alumni, 6 teaching lecturers, Head of the Laboratory & Business Incubation Center, Head of the Entrepreneurship Study Program, Dean of the Faculty of Economics & Business and Chancellor of Muhammadiyah University of Gresik. The results of this study are an effective entrepreneur education model that includes building an entrepreneur mentality, design workshops and seminars, project-based learning, and sustainable business/entrepreneur project courses. The success of forming young entrepreneurs is measured through the stages of the Entrepreneur Project, including the creation of new product/service prototypes with the principle of entrepreneur decision-making (Effectuation), validation of business models and product/service prototypes through customer testing, product launches with at least two repairs, and innovation. with 10 types of structured innovation. Student behavior shows enthusiasm for innovation, but the effectiveness of understanding in making business decisions still needs development